(untitled) (City: History, Culture, Society, 2021)
The article is devoted to the topical issues of developing the KhTZ district and the KhTZ plant as the object of the industrial heritage in the postindustrial society. The KhTZ district was created by famous Soviet architect and urban planner Pavlo Aloshyn as Sotsmisto, which could be opposed to the old Kharkiv and be built on the empty Losevo empty ground. The main element was the living cell, which contained housing and social infrastructure. In the arterwar time, this conception was left behind, although such an element is visible nowadays. The vast plants such as Electrovazhmash, the freezer plant, and the tile plant appeared. Now they do not work on their full production capacity and do not develop the social infrastructure. Nowadays, the KhTZ district, on the one hand, is the object of the architectural and industrial heritage. On the other hand, it is considered a degrading district. In the district, there are several civil and cultural initiatives formed, and they advocate for the social, infrastructural and ecological development of the district. Thus, in this text, we will highlight the main actors of revitalization and their cross-points and conflicts.